KRITIK MATAN HADIS Studi Komparatif antara al-A‘ẓamī dan G.H.A Juynboll - Masrukhin Muhsin (Holistic al-Hadis, 2016)
The traditional methods of criticism to the matn of ḥadîths (i.e. muqâranah and mu‘âraḍah) which are employed by the muḥaddithîn are claimed by M. M. Azami to be more accurate and comprehensive, in comparison to the common link method which is introduced by G. H. A. Juynboll. In principle, both muqâranah and mu‘âraḍah work by comparing a concept contained in a hadîth in question to the concept contained in Alqur’ân, Hadîth Mutawâtir, logic, and so on. Meanwhile, common link as a method only compares the wordings of simmilar ḥadîths in question. When the wordings are fitted, the ḥadîths are regarded as ṣaḥîḥ. In contrary, if the wordings are not compatible, the ḥadîths are then regarded weak.